Pengaruh Disiplin Kerja dan Pengalaman Kerja terhadap Kinerja Karyawan - Danil Prabowo; Suci Putri Lestari; Ari Arisman (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was conducted with the aim of determining the influence of work discipline and work experience on the performance of SPBE PT employees. Mitra Buana Energi Raya. The method used in this research is a survey method using data obtained directly through questionnaires distributed to 45 respondents who are employees of SPBE PT. Mitra Buana Energi Raya. The technique used in this research is multiple regression analysis. Based on research results, it is known that work discipline and work experience simultaneously have a significant effect on the performance of SPBE PT employees. Mitra Buana Energi Raya. Work Discipline partially has a significant effect on the Performance of SPBE PT Employees. Mitra Buana Energi Raya. Work experience partially has a significant effect on the performance of SPBE PT employees. Mitra Buana Energi Raya.